Stairways to Heaven: An Interlocking Self-Regulation Model of Negotiation - Brett, Joan F.; Northcraft, Gregory B.; Pinkley, Robin L. (Academy of Management Review, 1999)
Joan F. Brett, Gregory B. Northcraft, Robin L. Pinkley, Stairways to Heaven: An Interlocking Self-Regulation Model of Negotiation, The Academy of Management Review, Vol. 24, No. 3 (Jul., 1999), pp. 435-451